Flexural Performance of Beams Strengthened with FRP Laminates and Alternative U-Wrap Anchors - Sneha M. Varghese; Kiran Kamath; Rajiv Selvam; Surumi Rasia Salim (Civil Engineering Journal, 2024)
Premature debonding is identified as the main failure mode in reinforced concrete (RC) beams strengthened with externally bonded Fiber-Reinforced Polymer (FRP) laminates. This issue leads to the underutilization of FRP materials and needs to be addressed. Research has shown that end anchorage systems can effectively delay/mitigate delamination failures and enhance the performance of strengthened beams. FRP U-wraps are an effective means to prevent debonding failure; however, as open-form anchors, U-wraps cannot always guarantee complete resistance to debonding failures. This study proposes an alternative U-wrapping technique where the ends of the U-wraps are flared and inserted into the concrete substrate. The feasibility and effectiveness of this technique were studied by comparing it with conventional U-wraps. The experimental phase involved testing seven RC beams, each measuring 1.96×0.15×0.3 meters, under four-point bending. The results showed that the anchorage technique improved beam performance in terms of load-deflection behavior, failure modes, ductility, and FRP strain. Additionally, finite element simulations were conducted using Abaqus software to assess the effectiveness of the alternative U-wrap scheme. These models incorporated various nonlinear material constitutive laws, including cohesive zone modeling to replicate debonding failures at the CFRP-concrete interface. The numerical predictions were found to be in good agreement with the experimental test data. Doi: 10.28991/CEJ-2024-010-08-01 Full Text: PDF